Contrast-enhanced ultrasound (CEUS) is helpful for the characterization of solitary fibrous tumors of the pleura - Safai Zadeh, Ehsan; Görg, Christian; Findeisen, Hajo; Eckwolf, Philip; Dibon, Lea; Prosch, Helmut (Ultraschall in der Medizin - European Journal of Ultrasound, 2025)
To describe the perfusion patterns of solitary fibrous tumors of the pleura (SFTP) using contrast-enhanced ultrasound (CEUS).Between November 2012 and 2024, six patients with histologically confirmed SFTP underwent B-mode ultrasound (B-US) and CEUS. Parameters from the arterial phase, including flow-in pattern, extent of enhancement (EE; marked or reduced/absent), and homogeneity of enhancement (HE; homogeneous or inhomogeneous) were retrospectively analyzed.All 6 lesions displayed a flow-in perfusion pattern that originated from a peripheral point. Five lesions (83.3%) exhibited arterial hyperenhancement and 1 (16.7%) showed hypoenhancement. HE was inhomogeneous in 5 lesions (83.3%) and homogeneous in 1 (16.7%).On CEUS, all cases showed an arterial flow-in perfusion that originated from a peripheral point in an SFT, which could be a diagnostic clue for the non-invasive diagnosis of SFTPs. Given the risk of tumor seeding, direct surgical resection may be preferable to biopsy in these cases.
Keywords: solitary fibrous tumors of the pleura; CEUS; ultrasound; SFT; diagnosis